KINERJA PERANGKAT DESA DALAM PEMBERIAN PELAYANAN KEPADA MASYARAKAT DI DESA TALONTAM KEAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Febri Eka Sari (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2022)
Village government apparatus is an important part in providing better and optimal services to the community. Based on Law Number 6 of 2014 concerning Villages, it is stated that building a professional, efficient and effective village government is inseparable from optimal public services in the administration of village governance. This research is to determine the performance level of the village government in providing services to the community in Talontam Village, Benai District, Kuantan Singingi Regency. The theory used in this study is Holle (2011) which uses three indicators, namely increasing the quality and productivity of the implementation of government tasks and functions in the field of public services; Encouraging efforts to streamline service systems and administration, so that public services can be provided more efficiently and effectively; and Encouraging the growth of creativity, initiative and community participation in the development steps as well as in efforts to improve the welfare of the wider community. The method used in this research is descriptive qualitative. The results showed that Talontam village government officials were able to provide optimal service to the community, and made Talontam village the second best self-sufficient village in Kuantan Singingi